Choising the alternative conditions for the continuity of the work of the nitrate-selective electrode (Latakia University Journal -Basic Sciences Series, 2019)
Due to the absence of operational requirements and its unidentified solutions ,this study presented definition alternative analytical  and technical conditions for the continuation of  nitrate-selective electrode working. Many electrolytes were tested (ammonium sulfate, ammonium acetate and ammonium chloride). The technical and analytical conditions shows  that the best response which give the Nernst  slope of the electrode had been obtained by adding 0.5ml of ammonium sulfate (3mol / l), and the response time was 20sec, by the time that values stabilized  for 15sec. The study of pH effect on the electrode response also showed that electrode works within the range (2-8)  of  pH and that the best response was at pH = 5.5 by using acetic acid-sodium acetate buffer. The effect of temperature on the potential electrode was studied ,it showed that the Nernest electrode response realized within  the range  (18-37) C0of temperature.While Studying the effect of some interfering ions such as (OH-, HCO3-, CO32-,Cl-,NO2-) on the work of the electrode showed low values ​​of the coefficient of selectivity, which did not exceed 3×10-2 that the electrode was not affected by the presence of these ions. The chosen  conditions were experimented on standard solutions, which showed that the electrode is working within the range (10-4-10-1) mol / l of concentrations. When the concentrations was about 10-5mol/l  or less than that, it was necessary to soak the electrode in solution which has low concentration for at least one hour, and diluted  the taken volumes ten times . These technical and analytical conditions was applied  on standard solutions and environmental samples(water), which showed the accuracy ,correctly and authenticity of the measurements.